Improving the Personnel Management System of an Industrial Enterprise - Smyrnova, I.; Rudyka, K. (Економічний вісник Донбасу, 2019)
The article has analyzed the trend of development and advanced technology for the personnel of the company. The structure of the personnel organization is provided. It is numbed on a post-requisite basis to thoroughly know the knowledge and knowledge, and also the importance of knowing it. Entered into the organization's ambush, ambush improvements system and personnel management at the galley of professional advancement and appreciation of public relations. The following is the main aspect of financial management and personnel development for industrial enterprises. The special features of financial support for personnel in foreign companies are highlighted. The mechanism of managing industrial personnel has been scattered, a kind of front door to the end of all prizes in the first stage, only one way, but for the most part, for the first time career income).